Evolution of Hox 3'UTR regulation by alternative polyadenylation and microRNA regulation within twelve Drosophila genomes - Patraquim, Pedro Miguel Queirós do Patrocínio, 1985- (2011)
Tese de mestrado. Biologia (Biologia Evolutiva e do Desenvolvimento). Universidade de Lisboa, Faculdade de Ciências, 2010